Conferencia de Medellín y familia latinoamericana. Modelo eclesiológico como nuevo paradigma para el siglo XXI (2020)
The II General Conference of Latin American Episcopates held in the city of Medellín - Colombia, in the year 1968, was considered "The Second Vatican Council in Latin America", as it inculturated it in the new continent. This article selects chapter III (family and demography), takes the theme of the family as: formator of people, educator in the faith and promoter of development and selects five key concepts (salvation, holiness, sacramental life, unity and community of faith ), then makes a parallel with the ecclesiological models of the treatise on ecclesiology proposed by the Second Vatican Council; later he proposes the Latin American family as an ecclesiological model that faces the challenges posed by the XXI century and the conclusions.